Child-centered, Play-based Education and Future Competency - Inkyung Kim (Korea Development Institute (KDI), 2020)
The child-centered, play-based curriculum enhances young children's problem-solving skills and socio-emotional competences. As such, in order to firmly establish it within the education system and bolster its effectiveness, guardians and teachers must collaborate to support children's play activities, and a mutually beneficial learning community for teachers must be built. - To improve adaptability, education must focus on enhancing students' problem-solving skills. - In the child-centered, playbased curriculum, children experience the problemsolving process via selfdirected play with their teacher's support - Support from teachers should be based on the children's play experiences in and outside of the classroom. - For the new curriculum to take hold, a sufficient number of execution examples and analysis of its effects on children's competences are needed. - Class critiques, which provide actual examples of the curriculum in operation, were conducted as a form of teacher training. - The training was designed to improve teachers' educational beliefs, knowledge, and practices. - The training improved the teachers' ability to execute the child-centered, play-based curriculum. - Teachers found it difficult to share the children's experiences in the classroom with their guardians and to discuss measures on supporting the children's development. - Teacher training in the form of class critiques was effective in improving children's cool executive function and socioemotional competences. - Executive function is a problem-solving skill and a psychological competence with which individuals combine and apply accumulated information to fulfill a goal while controling their impulses and establishing an action plan, putting it into practice, and attempting a different strategy when the first fails. - Executive function can be divided into working memory, inhibition, and cognitive flexibility. - Teacher training enhanced children's inhibition and cognitive flexibility. - Executive function can serve as an indicator for children's problem behaviors and emotional control as well as their future experiences e.g. resilience, maintaining a job and marriage, health, income, and the crime rate. - Teacher training improved children's extrinsic and intrinsic problem behaviors and socio-emotional competences e.g. emotional self-control. - The child-centered, playbased curriculum creates an environment that can foster children's executive function. - The execution of the curriculum enhances children's executive function and improves their socioemotional competence either directly or via the executive function. - For the curriculum to take root and to be more effective, class critiques should be conducted in greater numbers, and collaboration is needed between teacher and guardians to support children's play.
Keywords: 330; Early Childhood Education